Special needs in the early years : snapshots of practice - Wolfendale, Sheila, 1939- (RoutledgeFalmer, 2000)
This book celebrates good practice in the area of early years and special needs by bringing together authors who are either practitioners or researchers from a range of settings including nurseries, schools and special provision units.